IMPLEMENTATION OF A MENTAL HEALTH AND MUSIC GROUP IN SUBACUTE REHABILITATION. (11th November 2018) - Strong, J V; Plys, E; Hartmann, C; McCullough, M
Abstract: Older adults in rehabilitation facilities are at high risk of developing or exacerbating existing mental health (MH) issues. Group MH treatment may be difficult to sustain for reasons specific to the rehabilitation setting, including conflicting appointments, high turnover of patients, and competition with other activities in the facility. This presentation focuses on the development and implementation process of the "Mental Health and Music" group (MH&M) in a VA Community Living Center (CLC). The MH&M was created as an 8-session, non-cumulative, non-sequential mental health intervention. The presenters will discuss the little-examined implementation process and examine issues piloting and evaluating the implementation. Finally, preliminary evaluation outcomes will be shared, including those related to affect, pain, and engagement in the group and across sessions.